2017
DOI: 10.1155/2017/8024857
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Combined with Rhodiola sacra Supplementation Improves Exercise Capacity and Ameliorates Exhaustive Exercise‐Induced Muscle Damage through Enhancement of Mitochondrial Quality Control

Abstract: Mounting evidence has firmly established that increased exercise capacity (EC) is associated with considerable improvements in the survival of patients with cardiovascular disease (CVD) and that antistress capacity is a prognostic predictor of adverse cardiovascular events in patients with CVD. Previous studies have indicated that aerobic exercise (AE) and supplementation with Rhodiola sacra (RS), a natural plant pharmaceutical, improve EC and enable resistance to stress; however, the underlying mechanism rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 52 publications
4
63
0
Order By: Relevance
“…It was further suggested that exercise preconditioning augmented mitophagy via H 2 O 2 oxidative stress-induced activation of PI3K [115]. Consistent with this view, it was found that earlier aerobic exercise complemented by a natural herb Rhodiola sacra protected the cardiac and skeletal muscles in exhaustive exercise through enhanced mitophagy [116]. Moreover, it has been demonstrated that exercise preconditioning may also exert protection against doxorubicin-induced cardiotoxicity [117].…”
Section: Mitophagy and Exercisementioning
confidence: 88%
“…It was further suggested that exercise preconditioning augmented mitophagy via H 2 O 2 oxidative stress-induced activation of PI3K [115]. Consistent with this view, it was found that earlier aerobic exercise complemented by a natural herb Rhodiola sacra protected the cardiac and skeletal muscles in exhaustive exercise through enhanced mitophagy [116]. Moreover, it has been demonstrated that exercise preconditioning may also exert protection against doxorubicin-induced cardiotoxicity [117].…”
Section: Mitophagy and Exercisementioning
confidence: 88%
“…With regards to the respiratory system, respiratory muscle dysfunction is a common manifestation in older patients with CVD [47], Tasoulis et al demonstrated that 12 weeks of HIIT significantly improved respiratory muscle function in older adults with HF [48]. With respect to skeletal muscle, we have previously shown that 4-weeks of aerobic exercise can enhance skeletal muscle mitochondrial biogenesis and function in male mice [49]. Motta et al [50] also showed that HIIT ameliorated fructose-induced metabolic dysfunction in male mice through mitochondrial biogenesis and β-oxidation, via irisin and PGC1 α in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…But the phosphorylation at S487 of AMPK in mechanical stress is unknown. And inhibition of AMPK activation significantly impaired mitochondrial function and increased the generation of ROS (Dun et al, ; Y. Chen et al, ). IL‐1β is a classic proinflammatory cytokine, so it is not surprising that it inhibits the expressions of AMPK‐α1 (phosphor S487) and IκB (inhibitor of NF‐κB)‐α (IκB‐α).…”
Section: Discussionmentioning
confidence: 99%